Management Strategies for Higher Education Institutions Based on the Principles of Education for Sustainable Development in the Lower Northern Region - Yuenyong, Trirat (Journal of Ecohumanism, 2024)
Education for sustainable development is globally acknowledged as crucial for fostering knowledge, skills, and values essential for sustainable living. This research aimed to (1) examine the current and desired conditions of administrative strategies in higher education institutions in the lower northern region based on the concept of education for sustainable development, and (2) develop corresponding strategies focusing on economic, social, environmental, and systemic dimensions. A mixed-method approach was employed, with a sample of 243 administrators and personnel from 12 universities in the region. Research instruments included a conceptual framework assessment, a questionnaire, and structured interviews. The findings revealed that current administrative practices ranked as follows: (1) curriculum development, (2) teaching and learning management, and (3) educational measurement and evaluation. While all aspects showed a good level of development, the desired conditions indicated the need for further improvement, with the ranking of (1) curriculum development, (2) educational measurement and evaluation, and (3) educational management. The study identified three core strategies: (1) reforming integrated curriculum design to align with sustainable development by emphasizing comprehensive systems that connect theory to practice; (2) enhancing the quality of educational measurement and evaluation to support sustainability-focused skills and concepts; and (3) transforming teaching and learning management by utilizing technology to foster an environment conducive to learning and innovation. These strategies are essential for guiding universities toward sustainable development and align with Thailand’s higher education standards focused on producing skilled, knowledgeable, and sustainability-minded graduates.